Variation in the HIF1A gene in elite rowers - Cieszczyk, P.; Kalinski, M.; Ostanek, M.; Jascaniene, N.; Krupecki, K.; Ficek, K.; Sawczuk, M.; Maciejewska, A. (The Journal of Strength and Conditioning Research, 2012)
The transcription factor hypoxia-inducible factor 1 (HIF1) is one of the key regulators of cellular metabolism. The aim of this study was to analyze the possible importance of the HIF1A Pro582Ser polymorphisms in rowing. One hundred twenty-seven male Polish rowers (both former and current competitors) were recruited for this study. Genotyping was carried out by polymerase chain reaction. Significance was assessed by Chi-square (x2) analysis. The results obtained revealed that frequency of the HIF1A Pro/Ser genotype (32.28 vs. 18.91%; p = 0.006) and Ser allele (16.93 vs. 10.00%; p = 0.01) were significantly higher in the rowers compared with those in controls. The results obtained confirm the significance of the HIF1A gene as a useful genetic marker in rowing. This kind of information would presumably be applicable in a program to search for the most predisposed individuals and also in the planning of training programs.